Parental burnout and adolescents’ academic burnout: Roles of parental harsh discipline, psychological distress, and gender - Zhang, Han; Li, Shujun; Wang, Ruimei; Hu, Qing (Frontiers in Psychology, 2023)
Parental burnout is an emerging hot issue in discussions about children’s mental health and development. However, little is known about the underlying psychological mechanisms of parental burnout on children’s academic burnout. To fill in this gap, we aim to examine the relationship between parental burnout and adolescents’ academic burnout, as well as the mediating effects of harsh discipline, adolescents’ psychological distress, and the moderating effect of gender. A sample of 871 junior high school students (477 boys and 394 girls) and their primary caregivers from Eastern China participated in this study. The results showed a direct relationship between parental burnout and academic burnout as well as an indirect relationship through the mediating role of psychological distress and the chain-mediating roles of parental harsh discipline and psychological distress. Furthermore, we discovered that fathers’ parental burnout had a stronger effect on children’s psychological distress than mothers. These findings contribute to our understanding of how parental burnout relates to children’s academic burnout and underline the significance of fathers’ parental burnout.